Student Perceptions of English Tense Learning Difficulties: A Mixed-Method Investigation in Pakistani Higher Education: https://doi.org/10.5281/zenodo.16924598 - Zainab Iqbal; Dr. Tariq (Corresponding author); Mohammad Israr; Salwa Shams (`, 2025)
Learning English tenses presents significant challenges for ESL students globally, particularly in Pakistan, where English serves as an official language and instructional medium in higher education. Despite extensive grammar instruction, students struggle with practical applications of the tense, creating gaps between theoretical knowledge and communicative competence. This study investigated undergraduate students' perceptions of difficulties in learning English tenses to identify problem areas and inform pedagogical improvements, employing a mixed-methods design that combined quantitative and qualitative approaches. From 256 English Department students at the University of Malakand, 110 were selected through stratified random sampling for questionnaires and 10 for semi-structured interviews. Data collection utilised a validated 30-item Likert scale questionnaire and an interview guide. Quantitative analysis employed descriptive statistics via SPSS 22.0, while qualitative data underwent six-step thematic analysis. Results showed students demonstrated confidence in basic tense structures and sentence recognition, but acknowledged difficulties with complex combinations, voice conversions, perfect continuous tenses, and temporal prepositions. The study recommends implementing communicative teaching approaches and addressing cognitive and affective factors in tense instruction. Keywords: English tense learning; student perceptions; ESL difficulties; mixed-method research